DIGITAL SOLUTIONS FOR A CLIMATE NEUTRAL ECONOMY: INTERNATIONAL FRAMEWORK OF ECO-DIGITAL PROJECTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The research reveals practical side of a twin green and digital transition in terms of a global path to climate neutral economy. Digitalization is considered as a driving force behind the transition towards a low-carbon economy. The article focuses on wide international experience of IT implementation for industrial decarbonization. Analytical database of the research covers more than 200 different eco-digital projects in various areas of climate regulations given by international organizations. This allows to outline international framework of eco-digital projects based on geolocation, regional features, IT decisions, level of technological support and climate influence. International differentiation of climate-digital projects was established by region. Comprehensive analysis of these data is provided to identify the gap in digital capabilities and climate targets. The rating of IT applied in climate-digital projects was built. As a result, the research proposes key project ways of the twin green and digital transition that are the most attractive for achieving climate neutrality on a global scale.